Podocyte-Specific Loss of Krüppel-Like Factor 6 Increases Mitochondrial Injury in Diabetic Kidney Disease - Horne, Sylvia J.; Vasquez, Jessica M.; Guo, Yiqing; Ly, Victoria; Piret, Sian E.; Leonardo, Alexandra R.; Ling, Jason; Revelo, Monica P.; Bogenhagen, Daniel; Yang, Vincent W.; He, John C.; Mallipattu, Sandeep K. (Diabetes (New York, N.Y.), 2018)
Mitochondrial injury is uniformly observed in several murine models as well as in individuals with diabetic kidney disease (DKD). Although emerging evidence has highlighted the role of key transcriptional regulators in mitochondrial biogenesis, little is known about the regulation of mitochondrial cytochrome c oxidase assembly in the podocyte under diabetic conditions. We recently reported a critical role of the zinc finger Krüppel-like factor 6 (KLF6) in maintaining mitochondrial function and preventing apoptosis in a proteinuric murine model. In this study, we report that podocyte-specific knockdown of Klf6 increased the susceptibility to streptozotocin-induced DKD in the resistant C57BL/6 mouse strain. We observed that the loss of KLF6 in podocytes reduced the expression of synthesis of cytochrome c oxidase 2 with resultant increased mitochondrial injury, leading to activation of the intrinsic apoptotic pathway under diabetic conditions. Conversely, mitochondrial injury and apoptosis were significantly attenuated with overexpression of KLF6 in cultured human podocytes under hyperglycemic conditions. Finally, we observed a significant reduction in glomerular and podocyte-specific expression of KLF6 in human kidney biopsies with progression of DKD. Collectively, these data suggest that podocyte-specific KLF6 is critical to preventing mitochondrial injury and apoptosis under diabetic conditions.